Q: What are the coefficients in this problem 3x - 4y plus 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

9x2 + 24xy + 16y2 = 9x2 + 12xy + 12xy + 16y2 = 3x(3x + 4y) + 4y(3x + 4y) = (3x + 4y)*(3x + 4y) = (3x + 4y)2

10x+4y+11xy

3x+4y+3 is ur answer, none of them are like terms so they can't be combineed

3x-3y

2x + 4y - 5x + 3y = 7y - 3x

Related questions

It is: 3x+4y which is an algebraic expression

9x2 + 24xy + 16y2 = 9x2 + 12xy + 12xy + 16y2 = 3x(3x + 4y) + 4y(3x + 4y) = (3x + 4y)*(3x + 4y) = (3x + 4y)2

plot 4y then 3x

10x+4y+11xy

You do not have enough information to solve this problem. More accurately, you do not have enough information to assign a numeric value to z. However, abstractly, you could say that z=27-3x-4y.

3x - 2y + 7x + 4y = 3x + 7x - 2y +4y = (3+7)x + (-2+4)y = 10x + 2y

(6x - 5y) + (-3x - 4y) =6x - 5y - 3x - 4y =3x - 9y =3 (x - 3y)

3x+4y+3 is ur answer, none of them are like terms so they can't be combineed

3x-3y

2x + 4y - 5x + 3y = 7y - 3x

4y = 3x+11 or as y = 3/4x+11/4

The answer is -5x + 2y. The terms with the same variable are combined by adding or subtracting their coefficients, and then the result is written with the corresponding variable. In this case, -3x and -2x combine to give -5x, and 4y and -2y combine to give 2y.